Enhanced electrocatalytic activity of PtRu/nitrogen and sulphur co-doped crumbled graphene in acid and alkaline media - Pang, Liuqing; Miao, Yuanyuan; Bhange, Siddheshwar N.; Barras, Alexandre; Addad, Ahmed; Roussel, Pascal; Amin, Mohammed A.; Kurungot, Sreekumar; Szunerits, Sabine; Boukherroub, Rabah (Journal of Colloid and Interface Science, 2021)
The low mass activity and high price of pure platinum (Pt)-based catalysts predominantly limit their large-scale utilization in electrocatalysis. Therefore, the reduction of Pt amount while preserving the electrocatalytic efficiency represents a viable alternative. In this work, we prepared new PtRu2 nanoparticles supported on sulphur and nitrogen co-doped crumbled graphene with trace amounts of iron (PtRu2/PF) electrocatalysts. The PtRu2/PF catalysts exhibited enhanced electrocatalytic performance and stability for the hydrogen evolution reaction (HER) at pH = 0. Moreover, the prepared PtRu2/PF electrocatalyst displayed higher HER activity than commercial 20% Pt/C. The PtRu2/PF catalyst achieved a current density of 10 mA cm(-2) at an overpotential value of only 22 mV for HER, performing better activity than many other Pt-based electrocatalysts. Besides, the PtRu2/PF revealed a good performance for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in alkaline media. The PtRu2/PF catalyst recorded a current density of 10 mA cm(-2) at an overpotential of only 270 mV for OER in KOH (1.0 M) solution and an onset potential of 0.96 V vs. RHE (at 1 mA cm(-2)) for ORR in KOH (0.1 M) solution. (C) 2021 Elsevier Inc. All rights reserved.
Keywords: HER; OER; ORR; PtRu2; Sulphur and nitrogen co-doped crumbled graphene

Improvement in oxygen evolution performance of NiFe layered double hydroxide grown in the presence of 1T-Rich MoS2 - Chakraborty, Soumita; Marappa, Shivanna; Agarwal, Sakshi; Bagchi, Debabrata; Rao, Ankit; Vinod, Chathakudath P.; Peter, Sebastian C.; Singh, Abhishek; Eswaramoorthy, Muthusamy (ACS Applied Materials & Interfaces, 2022)
NiFe layered double hydroxide (NiFe LDH) grown in the presence of MoS2 (rich in 1T phase) shows exceptional performance metrics for alkaline oxygen evolution reaction (OER) in this class of composites. The as-prepared NiFe LDH/MoS2 composite (abbreviated as MNF) exhibits a low overpotential (eta(10)) of 190 mV; a low Tafel slope of 31 mV dec(-1); and more importantly, a high stability in its performance manifested by the delivery of current output for 45 h. It is important to note that this could be achieved with an exceedingly low loading of 0.14 mg cm(-2). The mass activity of this composite (97 A g(-1)) is about 14 times greater than that of the conventional RuO2 (7 A g(-1) ) at eta = 200 mV. When normalized with respect to the total metal content, a mass activity of 1000 A g(-1) (eta = 300 mV) was achieved. Impedance analysis further reveals that the significant reduction in charge-transfer resistance and hence high current density (5 times greater as compared to NiFe LDH at eta = 300 mV) observed for MNF is associated with interfacial adsorption kinetics of intermediates (R-1). Significant enhancement in the intrinsic activity of MNF over LDH has been observed through normalization of current with the electrochemically active surface area. Computational studies suggest that the Ni centers in the composite act as the active sites for OER, which is well-corroborated with the observed postreaction appearance of Ni3+ species.
Keywords: Impedance; LDH-MoS2 hybrid electrocatalyst; mass activity; OER; overpotential

Nanocrystalline (NixCo(1-x))3(PO4)2@FeSe2/NF as a promising OER electrocatalyst for alkaline water electrolysis - Christi, Darren Sebastian; Selvaraj, Kaliaperumal (International Journal of Hydrogen Energy, 2024)
Affordable and sustainable hydrogen production is the need of the hour owing to the mounting global pursuit for the hydrogen economy. Water splitting is the premier go -to method to produce green hydrogen at a larger scale in which the half -cell Oxygen Evolution Reaction (OER) demands a larger amount of energy expenditure due to its sluggish kinetics. Hence, designing an efficient OER electrocatalyst, especially for alkaline water electrolysis that offers alternatives to the usage of precious group metals is a pressing priority. Herein, we report a novel nanocrystalline electrocatalyst consisting of two components, namely cobalt nickel phosphate and iron diselenide synthesised via a two-step electrodeposition at room temperature. The combination of the two components on the porous nickel foam substrate exhibits an overpotential of 272 mV at 100 mA/cm2 in 1 M KOH showing a low Tafel slope of a mere 38 mV/dec with appreciable retention even after 24 h of stability test at a relatively higher current density. The surface reconstruction that occurs when FeSe2 is electrodeposited on (Ni0.35Co0.65)3(PO4)2@NF and the synergy between the two components is the primary reason for the improved performance. Thus, this work highlights the ambient synthesis of a highly durable earth -abundant metal -based electrocatalyst which exceeds the performance of the standard Ru/C by a decent margin.
Keywords: Alkaline Water Electrolysis; Ambient synthesis; Electrodeposition; Non-PGM based Electrocatalyst; OER

Bifunctional nanoelectrocatalyst: semi-amorphous cobalt tungstate-based nanocomposites surpassing amorphous and crystalline counterparts - Dev, Sahil; Nagappan, Sreenivasan; Kundu, Subrata; Mukherjee, Shatabdi Porel (ACS Applied Materials & Interfaces, 2025)
Electrocatalytic water splitting to hydrogen and oxygen is considered to be one of the significant routes for future renewable energy conversion. Therefore, the development of unique, efficient, and cost-effective bifunctional electrocatalysts, which can perform both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), is critical for the accessible utilization of renewable energy. The increasing overall efficiency of the water-splitting reaction is pivotal for sustainable energy conversion and hydrogen production. Herein, we present a facile solution-based synthesis route to control the crystallinity of the cobalt tungstate (CoWO4) nanomaterials to amorphous, semiamorphous, and crystalline phases and further exploit these nanomaterials as bifunctional electrocatalysts for the HER, OER, and overall electrochemical water splitting reaction. Notably, the semiamorphous cobalt tungstate nanomaterials show a remarkable surface area of approximately 150 m(2)/g, the highest reported for CoWO4-based materials, and demonstrated superior activity for both the OER and HER and outstanding stability over the amorphous and crystalline counterparts. Notably, the SemiAmp||SemiAmp electrolyzer demonstrated a better performance for overall water splitting than the commercial RuO2||Pt/C electrolyzer.
Keywords: amorphous; CoWO4; electrocatalyst; HER; Nanocomposite; OER; water splitting

Growth of Mo-doped Ni3S2 nanorods array for superior overall water splitting reaction - Sharma, Pooja; Khandare, Lina; Saha, Arindam; Chaure, Nandu B.; Yengantiwar, Ashish (International Journal of Hydrogen Energy, 2025)
Designing novel, efficient and cost-effective dual-functional electrocatalyst for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) using an alkaline electrolyte is crucial for establishing a sustainable hydrogen economy and transitioning to a society powered by renewable energy sources. In the present work, Mo-doped nickel sulfide (Mo-Ni3S2) nanorods were grown on Ni-treated nickel foam (N-NF) substrate via a two-steps hydrothermal method. Specifically, Mo-Ni3S2/N-NF surface consists of nanorods-like morphology, which provides extensive area for percolation of electrolyte, that resulting in outstanding catalytic performance. Such a well-synthesized electrode exhibited superior performance and stability for OER as compared with pristine Ni3S2/NF and bare nickel foam (NF) electrodes. In addition, Mo-Ni3S2/N-NF electrode provides good HER activity and confirms its dual-functionality in alkaline medium. Our champion Mo-Ni3S2/N-NF electrocatalyst delivers best OER overpotential of 230 mV at current density of 100 mA/cm(2). Also, it provides HER overpotential of 100.6 mV at a current density of 10 mA/cm(2). Both OER and HER are carried out in the presence of 1 M KOH alkaline electrolyte. OER stability of the best-performed Mo-Ni3S2/N-NF electrode demonstrates almost constant current density similar to 120 mA/cm(2), which retains 90% of original value after continuously tested for the duration of 22 h. The total cell voltage of 1.56 V is provided by Mo-Ni3S2/N-NF integrated system and it demonstrates a good stability for duration of 22 h. Our approach provides a new insight into developing earth-abundant, inexpensive and superior dual-functional electrocatalyst for overall water splitting reaction (WSR).
Keywords: Dual-functional electrocatalyst; HER; Mo doping; Nickel sulfide nanorods; OER; overall water splitting

Harnessing AEM electrolyzer-level performance through strategically designing the electronic structure of electrocatalysts, enabling dynamic functional switching - Kumar, Sonu; Verma, Tushar Singh; Selvaraj, Kaliaperumal (ACS Catalysis, 2025)
The anion exchange membrane water electrolyzer (AEMWE) is a promising technology for cost-effective hydrogen production. To promote its development and adoption, targeted efforts are focused on finding non-platinum group metal (non-PGM) electrocatalysts that efficiently facilitate the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). Nickel sulfides (NiS) are effective OER catalysts; however, they suffer due to leaching-related instability at electrolyzer stack operational conditions. We introduce a rational non-PGM design that enhances stability during the OER while excelling at the HER, showcasing molecular-level insights for a scalable AEMWE zero-gap stack device. NiS coating is applied to the Al-metal-organic framework supported by 3D porous nickel foam (NSMA), leading to charge localization at the interface, which helps in OER by requiring only 322 millivolts at 100 mA cm-2. The main innovation in the NSMA design is a controlled electroreduction process that converts the Millerite phase into Ni3S2, a catalyst (rNSMA). This transformation leads to charge delocalization at the surface and a low overpotential of -80 mV at -100 mA cm-2 for the HER. In a full cell, this catalyst duo requires an overpotential of 1.49 V, outperforming the commercial Pt/Ru catalyst pair at 1.58 V. In a scaled-up 12.96 cm2 AEM electrolyzer single-cell stack, current density rose from 398 to 1062 mA/cm2, maintained for over 100 h at high temperatures, achieving 99% Faradaic efficiency and 100% hydrogen purity. The AEM electrolyzer cell shows a good energy efficiency of 45.50 kWh/kg and a cell efficiency of 86.59%. Detailed studies, including DFT analyses, revealed that electronic structure modification enhances charge delocalization, driving its impressive performance on an industrially significant scale.
Keywords: anion exchangemembrane water electrolyzer (AEMWE); charge transfer; density functional theory(DFT); HER; nickel sulfide; OER

Self-supported super-hydrophilic interconnected nanospikes and particles of MoS2-Ni3S2/NF with optimum d-band center for anion exchange membrane water electrolyzer - Kumar, Yogesh; Barik, Sidharth; Samudre, Nikhil S.; Kharabe, Geeta Pandurang; Chauhan, Inderjeet; Manna, Narugopal; Bhat, Suresh; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
There is an imperative need for highly efficient electrocatalysts for cost-effective hydrogen production. Herein, a self-supported, hybrid composite as a bifunctional electrocatalyst is introduced. This is achieved by in situ growth of MoS2-Ni3S2 on nickel foam (NF), designated as MoS2-Ni3S2/NF, synthesized by a facile one-step hydrothermal synthesis method. MoS2-Ni3S2/NF exhibits low overpotentials of only 187 and 146 mV for OER and HER, respectively, to achieve a current density of 10 mA cm-2 in 1 M KOH. The practical application of the designed bifunctional electrocatalyst is verified by constructing the MoS2-Ni3S2/NF || MoS2-Ni3S2/NF symmetrical membrane electrode assembly (MEA) of 4 cm2 working area for the anion exchange membrane water electrolyzer. The system shows continuous electrolysis for the monitored 48 h duration. For OER, an optimum d-band center of -1.66 eV for the heterostructure is calculated from the Density Functional Theory (DFT) studies. The factors like the unique structure of the electrocatalyst, enhanced hydrophilicity, improved electrochemically accessible number of sites (ECASs), and optimum d-band center, are expected to be the primary contributors to the system's improved performance. Thus, the present finding unveils a straightforward synthesis approach for creating a stable electrocatalyst for advancing commercial water electrolysis in the realm of renewable electrochemical energy conversion.
Keywords: AEM; d-band center; electrolyzer; HER; OER